Enhancing Light Emission in Interface Engineered Spin‐OLEDs through Spin‐Polarized Injection at High Voltages. Issue 10 (15th January 2019) - Prieto‐Ruiz, Juan Pablo; Miralles, Sara Gómez; Prima‐García, Helena; López‐Muñoz, Angel; Riminucci, Alberto; Graziosi, Patrizio; Aeschlimann, Martin; Cinchetti, Mirko; Dediu, Valentin Alek; Coronado, Eugenio
Abstract: The quest for a spin‐polarized organic light‐emitting diode (spin‐OLED) is a common goal in the emerging fields of molecular electronics and spintronics. In this device, two ferromagnetic (FM) electrodes are used to enhance the electroluminescence intensity of the OLED through a magnetic control of the spin polarization of the injected carriers. The major difficulty is that the driving voltage of an OLED device exceeds a few volts, while spin injection in organic materials is only efficient at low voltages. The fabrication of a spin‐OLED that uses a conjugated polymer as bipolar spin collector layer and ferromagnetic electrodes is reported here. Through a careful engineering of the organic/inorganic interfaces, it is succeeded in obtaining a light‐emitting device showing spin‐valve effects at high voltages (up to 14 V). This allows the detection of a magneto‐electroluminescence (MEL) enhancement on the order of a 2.4% at 9 V for the antiparallel (AP) configuration of the magnetic electrodes. This observation provides evidence for the long‐standing fundamental issue of injecting spins from magnetic electrodes into the frontier levels of a molecular semiconductor. The finding opens the way for the design of multifunctional devices coupling the light and the spin degrees of freedom. Abstract : Spin‐polarized injection in the frontier electronic levels of a molecular semiconductor is demonstrated in a specially designed spin‐polarized organic light‐emitting diode. In this multifunctional spintronic device, the charge injection is optimized through the tailoring of the energy‐level alignment between the molecule's frontier orbital and the electrode's work functions. An enhancement in the magneto‐electroluminescence up to 2.4% is observed.